Metal supported carbon nanostructures for hydrogen storage - Matelloni, Paolo (2012)
Carbon nanocones are the fifth equilibrium structure of carbon, first synthesized in 1997. They have been selected for investigating hydrogen storage capacity, because initial temperature programmed desorption experiments found a significant amount of hydrogen was evolved at ambient temperatures. The aim of this thesis was to study the effect of impregnation conditions on metal catalyst dispersion and to investigate whether the metal loaded cones had improved hydrogen storage characteristics. Pre-treatment of carbon nanocones with hydrogen peroxide was carried out, followed by metal decoration in aqueous solution by an incipient wetness technique. Two methods of reducing the metal catalyst have been applied: in hydrogen at room temperature (RT) and in an aqueous solution of NaBH4. X ray diffraction (XRD) technique confirmed the complete metal reduction and transmission electron microscope (TEM) analysis showed that the reduction technique affected the catalyst dispersion. Very fine dispersions of ca. 1 nm diameter metal clusters at catalyst loadings of 5 wt% were achieved and high dispersions were retained for loadings as high as 15 wt%. Hydrogen uptakes at RT were measured and an increase with metal loading was observed. In comparison the same route of pre-treatment and metal impregnation has been done over graphite nanofibres (GNF) and the hydrogen uptake showed an adsorption superior of the cumulative contribution of the substrate and metal catalyst attributing this to hydrogen spillover.